ORGANIZING FOR RESILIENCE leading and managing risk in a disruptive world - Williams, Christopher 1966-; You, Jacqueline Jing (ROUTLEDGE, 2021)
Organizing for Resilience provides a fresh and novel insight into research on how leaders can prepare their organizations to face up to shocks and disruptions in a turbulent and unpredictable world. It provides an analysis of the topic of organizational resilience in a comprehensive and integrative way, with fresh theoretical and research implications as well as important implications for leaders. The first book to synthesize themes from across a spectrum of resilience using the metaphor of a 'resilience landscape', chapters in Part I are devoted to five analytical levels: individual level resilience; small firms in which major disruption can threaten survival; large firms with disruptions in one part of the organization; large firms facing enterprise-wide disruption; and disruption to a complete community or economic ecosystem of individuals and organizations. Cases and practice insights are presented to bring the topics to life, allowing reflection and debate at each level. In Part II, the construct of the 'resilience landscape' is developed, along with a discussion on leadership for resilience by instilling a resilience mind-set and developing capabilities in relational resilience. The book is ideally suited to bachelor's and master's degree courses on strategy, organizational behaviour and leadership. PhD and DBA researchers in the field of resilience and strategy will also find the book useful, as will practising consultants and business leaders.